Incentives, Supervision, and Sharecropper Productivity - Jacoby, Hanan G.; Mansuri, Ghazala (2012)
Though sharecropping remains widespread, its determinants are still poorly understood and the debate over the extent of moral hazard is far from settled. We address both issues by analyzing the role of landlord supervision. When landlords vary in their cost of supervision, otherwise identical share-tenants can have different productivity. Unique data on monitoring frequency collected from share-tenants in rural Pakistan confirms that, controlling for selection, 'supervised' tenants are significantly more productive than 'unsupervised' ones. Also, landlords' decisions regarding monitoring and incentives offered to tenants depend importantly on the cost of supervision.